The Provision Of Employment Opportunities For Workers With Disabilities According To Law Number 8 Of 2016 On Persons With Disabilities Jo. Law Number 13 Of 2003 On Labor In Pt. Sinar Desa Rawa, Cingambul District, Majalengka Regency - Putri Erina Reyhana; Deddy Effendy (Bandung Conference Series: Law Studies, 2024)
People with disabilities have different conditions, some have physical disabilities, mental disabilities, and a combination of physical and mental disabilities. The condition of people with disabilities affects their ability to participate in society, so they need support and assistance from others. People with disabilities also face greater difficulties than non-disabled people, such as barriers in accessing public services, education, health, and employment. To provide employment opportunities for people with disabilities, the government, state-owned and private companies, and civil society must ensure the elimination of various legal and social barriers in employing people with disabilities. This study aims to find out how the Implementation of the Right to Get a Job for Workers with Special Needs at PT. Sinar based on Law number 8 of 2016 concerning Persons with Disabilities which is related to Law number 13 of 2003 concerning Labor and to find out the efforts of the company in providing facilities for Persons with Disabilities.The method used in this study uses a normative juridical approach, which is research conducted by examining and comparing literature sources in the form of Labor Law and various kinds of literature and research specifications, namely descriptive analytical, which is an analysis of the applicable legal provisions and analyzed using relevant legal policy theories.Based on the research results, it is known that PT. Sinar in Majalengka Regency has not implemented what is mandated in Law Number 8 of 2016 concerning Persons with Disabilities. The right to get a job for people with disabilities has not been fulfilled and is not in accordance with what is mandated in Law Number 13 of 2003 concerning Labor. There is still discrimination against people with disabilities in the company. The company’s efforts in providing facilities for workers with disabilities have not been fulfilled, and are not in accordance with the law number 8 of 2016 concerning persons with disabilities regarding the company’s efforts in providing assistive devices to support work and accessibility for people with disabilities.